Determinants of loss to follow-up among people living with HIV receiving antiretroviral therapy in a universal test and treat setting: A retrospective cohort study in Nepal - Archana Shrestha; Lisasha Poudel; Bikram Adhikari; Saroj Bhandari; Roman Shrestha; Rajya Shree Kunwar; Lok Raj Pandey; Man Bahadur KC; Erin C. Wilson; Keshab Deuba (Public Health in Practice, 2025)
Objectives: This study aims to assess the cumulative incidence and rate of loss to follow-up (LTFU) among people living with HIV (PLHIV) in Nepal who begin antiretroviral therapy (ART) early, as well as to identify factors associated with LTFU in the context of the universal test and treat approach. Study design: Retrospective cohort study. Methods: We retrospectively analysed nationally representative routine programme data for all PLHIV initiated on ART from February 19, 2017, to February 18, 2020, and followed up until May 10, 2022. LTFU was defined as a client not returning to the HIV clinic for at least 3 months from the date of their last scheduled appointment. We calculated cumulative incidence rate (IR) and used a multivariable Cox proportional hazards regression model to identify factors associated with LTFU, reporting corresponding 95% confidence intervals (CI). Results: Of the 8192 clients included in our sample, 6797 (82.9 %) started ART within seven days following their HIV diagnosis. The overall IR of LTFU was 4.22 (95 % CI = 3.95–4.51) per 100 person years of observation. The cumulative incidence of LTFU increased over time on ART, from 3.81 % (95 % CI = 3.40–4.26) at 6 months, 6.51 % (95 % CI = 5.97–7.09) at 12 months to 13.41 % (95 % CI = 12.51–14.37) at 48 months. In the multivariable model, factors associated with higher odds of LTFU included initiating treatment within 7 days of diagnosis, younger age, being unmarried, belonging to the Dalit caste, having WHO clinical stage 1 at baseline, and initiation on a non-nucleoside reverse transcriptase inhibitors (NNRTI)-based regimen. Among key populations, sex workers, their clients, men who have sex with men and transgender, people who inject drugs were at higher risk of dropout compared to migrants. Conclusions: In this nationwide cohort, the risk of LTFU increased with time on ART. To optimize the test-and-treat strategy in Nepal, it is crucial to address the unique needs of youth and certain key populations and manage any early adverse drug reactions.